Increase in self-reported empathy during medical school training: A longitudinal study - Nieves Díez; María Cristina Rodríguez-Díez; Leire Arbea; José Pereira; Fermín Rodríguez; Marcos Trelles; Alfredo Gea; Loreto García del Barrio (PLoS ONE, 2025)
Background Empathy is a fundamental tool in clinical practice, but despite its importance and benefits, it is often underrepresented in medical curricula. This study explored the evolution of medical students’ empathy longitudinally across six years of undergraduate training following the introduction of a curriculum with 4-hour workshops during each of the six clinical rotations from Years 4 to 6, complemented by self-reflections after each rotation. Methods Students of the 2016 class (graduated 2022) completed the Jefferson Scale of Empathy-Students (JSE-S) and the Interpersonal Reactivity Index (IRI) at the beginning of Year 1 (T0) of studies, beginning Year 3 (T1), end Year 3 (T2) and end Year 6 (T3). The NEO Five-Factor Personality Inventory was completed at T0. Empathy scores across timepoints were analyzed using repeated measured analyses of variance (ANOVA). Results 36.1% and 32.5% of 169 eligible students completed the JSE-S and IRI scores respectively at all four timepoints. The JSE-S total mean score increased significantly across the six years of medical course (p < 0.001), as did the IRI total mean score (p < 0.001). In addition, the mean JSE-S total score increased significantly between T3 vs T0 (p < 0.001), T3 vs T2 (p < 0.001 and T2 vs T1 (p = 0.028); and the mean IRI total increased significantly between T3 vs T0 (p < 0.001) and T3 vs T2 (p < 0.001). Conclusion Medical students who experienced a new professionalism program increased their empathy as measured by the JSE-S and IRI instruments across the six years of curriculum.